UI/UX DESIGN OF D'PARAGON EMPLOYEE ATTENDANCE SYSTEM USING THINGKING DESIGN METHOD - Prabowo, Iwan Ady; Kumarahadi, Yofita Kinanti; Heradi, Ade Miraldha (STMIK Sinar Nusantara, 2023)
The purpose of this thesis is to help D'Paragon company to make changes to the absence system that still uses finger print to the absence system model using a mobile application. The company has several employees who may not be able to be absent again at the central location because there are several tasks that must be carried out in several locations other than the central location. Therefore, an online attendance system was created using a mobile-based attendance system. The author will design the UI/UX display of the attendance application to make it easier for developers to design applications, which can later be used for employee attendance. The research method used is the Design Thinking method. This method is known as a comprehensive thinking process that concentrates on creating solutions that begin with a process of empathy for a particular human-centered need. There are 5 stages in this method, namely Empathize, Define, Ideate, Prototype, and Testing.